GE_GERICHTE C/15535/2013 vom 17. Januar 2014 - GE Cour de justice (2014)
CÉDULE HYPOTHÉCAIRE SUR PAPIER; CESSION DE CRÉANCE(CO); CRÉANCE; SUBROGATION; MAINLEVÉE PROVISOIRE | CC.827; CC.842; CO.165.1; LP.82